The impact of group psychological abuse on distress: the mediating role of social functioning and resilience - Emma Antelo; Omar Saldaña; Álvaro Rodríguez-Carballeira (European Journal of Psychotraumatology, 2021)
Background: Previous studies indicate that social functioning and resilience can mitigate the adverse psychological effects of interpersonal violence. Unfortunately, the role of these variables has not been studied in survivors of groups, organizations, and communities in which psychological abusive strategies are inflicted to recruit and dominate their members. Objective: To examine the mediating role of social functioning and resilience in the relationship between psychological abuse experienced in the past while in a group and current psychosocial distress and psychopathological symptoms. Method: In this cross-sectional study, an online questionnaire was administered to 794 English-speaking former members of different kinds of groups, such as religious, pseudo therapeutic, pyramid scheme groups, and others. Among them, 499 were victims of group psychological abuse and 295 were non-victims. Results: Victims of group psychological abuse reported lower levels of social functioning and resilience than non-victims, and higher levels of psychosocial difficulties and psychopathological symptoms. Serial mediation analyses revealed that social functioning and resilience mediated part of the impact of group psychological abuse on psychosocial difficulties and psychopathological symptoms. Sex and age joining the group were included as covariates. Participants who had experienced higher levels of group psychological abuse tend to have poorer social functioning, which is related to lower resilience. In turn, lower levels of social functioning and resilience are related with higher distress. Conclusions: This research sheds light on the underlying mechanisms involved in the relationship between group psychological abuse and distress suffered following this kind of traumatic experiences. Findings highlight the protective role of social adjustment, which can help promote and enhance resilience and mitigate psychosocial difficulties and psychopathological symptoms in survivors of group psychological abuse.